Ð”Ð¸Ð½Ð°Ð¼Ñ–ÐºÐ° Ð¿ÑÐ¸Ñ…Ð¾Ñ„Ñ–Ð·Ñ–Ð¾Ð»Ð¾Ð³Ñ–Ñ‡Ð½Ð¸Ñ… Ð¿Ð¾ÐºÐ°Ð·Ð½Ð¸ÐºÑ–Ð² Ñƒ Ð¶Ñ–Ð½Ð¾Ðº, ÑÐºÑ– ÑÑ‚Ñ€Ð°Ð¶Ð´Ð°ÑŽÑ‚ÑŒ Ð½Ð° Ð´ÐµÐ¿Ñ€ÐµÑÐ¸Ð²Ð½Ð¸Ð¹ Ñ€Ð¾Ð·Ð»Ð°Ð´ Ð· Ð°ÑƒÑ‚Ð¾Ð°Ð³Ñ€ÐµÑÐ¸Ð²Ð½Ð¾ÑŽ Ð¿Ð¾Ð²ÐµÐ´Ñ–Ð½ÐºÐ¾ÑŽ Ð¿Ñ–Ð´ Ð²Ð¿Ð»Ð¸Ð²Ð¾Ð¼ ÐºÑ€Ð°Ð½Ñ–Ð¾Ñ†ÐµÑ€ÐµÐ±Ñ€Ð°Ð»ÑŒÐ½Ð¾Ñ— Ð³Ñ–Ð¿Ð¾Ñ‚ÐµÑ€Ð¼Ñ–Ñ— - Bacherykov, A. N.; Tkachenko, T. V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
The dynamics of psychophysiological functions in women with depressive disorders accompanying with an autoagressive behavior in the process of treatment with application of craniocerebral hypothermia (CCH) was analyzed. It is shown that the application of CCH results in recovery of cognitive functions, decrease of level of reactive anxiety.